Exploring Financial Well-Being: Concept, Measurement, and Emerging Challenges (GESTIÓN Y TENDENCIAS, 2023)
This article examines the theoretical evolution of financial well-being, highlighting its shift from a perspective focused exclusively on income and economic resources toward a multidimensional approach that integrates psychological, social, and behavioral factors. It reviews various definitions and measurement instruments, such as the Personal Financial Wellness (PFW) scale and conceptual models that incorporate both the objective state of resources and the individual's subjective satisfaction and perception. The analysis identifies key determinants of financial well-being, including socioeconomic factors, the role of financial stress, and behaviors such as self-control. Finally, it discusses emerging challenges such as financial exclusion and the impact of Fintech, underscoring the need for multidisciplinary approaches to future financial education and regulation.
Keywords: financial well-being; economic psychology; financial exclusion; psychometric measurement; financial behavior